En qué punto se encuentra el acceso abierto. Cómo medirlo - Gargiulo, Paola (Anuario ThinkEPI, 2015)
Reseña de tres informes:Â Archambault, Eric;Â  Amyot, Didier;Â  Deschamps,Philippe;Â  Nicol, Aurore;Â  Rebout, Lise;Roberge, Guillaume (2013). Proportion of open access peer reviewed papers at European level and worldwide - 2004-2011. European Commission DG Research; Innovation Science-Metrix Inc.http://www.science-metrix.com/pdf/SM_EC_OA_Availability_2004-2011.pdfÂ Caruso, Julie;Â  Nicol, Aurore;Â  Archambault, í‰ric (2013). Open access strategies in the European Research Area. European Commission DG Research & Innovation Science-Metrix Inc.http://www.science-metrix.com/pdf/SM_EC_OA_Policies.pdfÂ Nicol, Aurore;Â  Caruso, Julie;Â  Archambault, í‰ric (2013). Open data policies and strategies in the European Research Area and beyond. European Commission DG Research; Innovation Science-Metrix Inc.http://www.science-metrix.com/pdf/SM_EC_OA_Data.pdf